Interactive Quantum Mechanics Quantum Experiments on the Computer - Brandt, Siegmund; Dahmen, Hans Dieter; Stroh, T. (Springer New York : Imprint: Springer, 2011)
Extra Materials available on extras.springer.com INTERACTIVE QUANTUM MECHANICS allows students to perform their own quantum-physics experiments on their computer, in vivid 3D color graphics. Topics covered include: •        harmonic waves and wave packets, •        free particles as well as bound states and scattering in various potentials in one and three dimensions (both stationary and time dependent), •        two-particle systems, coupled harmonic oscillators, •        distinguishable and indistinguishable particles, •        coherent and squeezed states in time-dependent motion, •        quantized angular momentum, •        spin and magnetic resonance, •        hybridization. For the present edition the physics scope has been widened appreciably. Moreover, INTERQUANTA can now produce user-defined movies of quantum-mechanical situations. Movies can be viewed directly and also be saved to be shown later in any browser. Sections on special functions of mathematical physics, coordinate systems and units, over 300 class-tested problems with hints for solutions, and a complete user's guide to the INTERQUANTA program are also included. No programming or computer experience is needed to use INTERQUANTA. Its Java™-based interface is as simple to use as surfing the Internet. Features of the INTERQUANTA program include: •        easy-to-use interface allowing fast change of physics parameters, •        demonstrations for each chapter illustrating new physical concepts and features of INTERQUANTA, •        electronic help files guiding users through the program, •        simple printing of user-produced graphics. INTERQUANTA runs on: •        personal computers under Windows® and Linux, •        Macintosh computers under Mac OS X.(INTERQUANTA was tested on 32-bit systems under Windows® 98, NT, 2000, ME, XP, Vista, and 7, under Linux Kernel 2.6.13, and under Mac OS X 10.4.11 for PowerPC and x86 processors. On 64-bit systems it was tested under Windows 7, Linux Kernel 2.6.28, and Mac OS X 10.6.4 for x86_64 processors.) INTERQUANTA's virtual "quantum mechanics laboratory" is a uniquely innovative approach to this important but abstract field of physics, and will benefit any student of quantum mechanics.